EFFICACY OF DIODE LASER IN THE MANAGEMENT OF GLAUCOMA FOLLOWING INTRAVITREAL SILICONE OIL INJECTION IN COMPLICATED RETINAL DETACHMENT - Ahmed, Nasir; Pir Salim Mahar; Aziz Ur Rehman; Abdul Qadeem Soomro; Asim Ateeq; Israr Ahmed Bhutto; Younus, Maryam (Journal of Ayub Medical College Abbottabad, 2021)
Background: Intravitreal silicone oil injection has been used to manage complicated retinal detachment. This study aims to analyse the efficacy of diode laser (TSCPC) in the management of secondary glaucoma following intravitreal silicone oil injection in complex retinal detachment surgery. Methods: The medical records of 58 eyes of 58 patients retrospectively were reviewed. Patients who underwent TSCPC for the management of secondary glaucoma following intravitreal silicone oil injection in complex retinal detachment were included. Procedure performed under local anaesthesia. The laser power was set at 1500-2200 mW for 2 sec. At each follow-up visit, patients went under charting of their IOP measurements with anterior segment and fundus examination. Post procedural follow up visits were carried out as; at 1 week, 1st, 3rdand 6thmonths. The efficacy was measured as reduction in IOP up to ‰¤20 mmHg without further needs for medications at 6 months. Results: The IOP was reduced up to 19.26±10.15 mmHg. Comparisons of IOP at each interval with pre-treatment showed significant difference with p<0.0001. The efficacy of procedure was achieved in 77.6% patients. Age, gender and pre-operative IOP showed significant association with p<0.05. Conclusion: Diode laser TSCPC was effective and safe in reducing IOP. The IOP decreases gradually over six month follow up. The procedure is simple and cost-effective yet reasonably afforded by patients in low resources population. In spite of the retained intravitreal silicon oil patients with failed medical treatment for uncontrolled IOP can be treated with TSCPS.